REASSESSMENT OF FIXED ASSETS IN PETROLEUM LICENSING CONTRACTS IN ACCORDANCE WITH INTERNATIONAL FINANCIAL REPORTING STANDARDS AND THEIR IMPACT ON THE QUALITY OF FINANCIAL REPORTING - Between Hamid Jassim; Asst. Prof.dr. Manal Hussein Lafta (Scholar Express Journals, 2022)
The research aims to clarify the concept of fixed assets, especially fixed assets, petroleum licensing contracts, on the one hand, and to present and analyze some accounting standards related to those assets, on the other hand. The measurement and accounting disclosure of fixed assets in petroleum licensing contracts is necessary to rely on accounting information by decision makers within The economic unit and outside the International Accounting Standard (IAS16) has allowed the use of the re-evaluation approach to measure assets in petroleum licensing contracts due to the inappropriateness of accounting information resulting from the application of the historical cost approach in light of the increase in technical and continuous developments that leave their clear effects on tangible non-current assets. The study begins by investigating the problem of the possibility of reassessing the fixed assets of petroleum licensing contracts in extractive companies and reporting them according to financial reporting standards. Where the research was based on the hypothesis that (the re-evaluation of the fixed assets of the petroleum licensing contracts in the Iraqi units leads to an improvement in the quality of reporting, which brings benefit to the users of the financial statements and financial statements. In order to achieve the objectives of the research, the researcher applied it to (Al Was at Oil Company).
Keywords: fixed assets; petroleum licensing contracts; international accounting standards